The Effect Of Democratic Behavior And Discussion Methods On Students' Learning Achievement In The Citizenship Education Subject In Grade XI IPS Of State High School 3 Pematangsiantar Academic Year 2025/2026 - Debora Kristiani Siahaan; Sepriandison Saragi; Sabar Dumayanti Sihombing (CV Putra Publisher, 2025)
Civics Education (PKn) learning plays a strategic role in shaping democratic character while improving student achievement. However, learning practices in schools still tend to be teacher-centered and involve minimal active student participation. This study aims to analyze the influence of democratic behavior and discussion methods on student achievement in Civics Education for grade XI IPS at SMA Negeri 3 Pematangsiantar in the 2025/2026 academic year. This study uses a quantitative approach with a correlational design. The study population was 142 students, with a sample of 28 students determined through purposive random sampling technique. The data collection instrument was a questionnaire to measure democratic behavior and the application of discussion methods, as well as documentation of student achievement scores. Data were analyzed using simple linear regression tests, multiple linear regression, linearity tests, and correlation tests with the help of the SPSS program. The results showed that democratic behavior had a positive and significant effect on student achievement, discussion methods also had a positive and significant effect on learning achievement, and there was a strong simultaneous influence between democratic behavior and discussion methods on student achievement. These findings confirm that civics learning that emphasizes the internalization of democratic values ​​through discussion methods can create a participatory learning environment, enhance student understanding, and strengthen civic character. Therefore, consistent application of discussion methods and strengthening of students' democratic behavior need to be optimized in civics learning.